2019
DOI: 10.5888/pcd16.180624
|View full text |Cite
|
Sign up to set email alerts
|

Single Cigar Price and Availability in Communities With and Without a Cigar Packaging and Pricing Regulation

Abstract: Single cigars are available for sale throughout the tobacco retail environment, are often sold for prices as low as 49 cents, and are available in flavors that appeal to youth. Since 2012, 151 municipalities in Massachusetts have enacted a minimum cigar packaging and pricing regulation that increases the price of a single cigar to a minimum of $2.50 and the price of multi-packs of 2 cigars to a minimum of $5.00. We used pricing data collected from retailers across the state to measure the effect of the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…However, despite a limited evidence base for cigars, policies mandating minimum pack sizes for cigars have been enacted in over 200 municipalities, primarily in Massachusetts, Minnesota, California, and New York [ 30 , 31 , 32 , 33 ]. Preliminary analyses of the effects of the policies enacted in Boston and Minnesota indicate the policies reduced single cigar availability, increased cigar sale price, and reduced disparities in access across neighborhoods [ 32 , 33 , 34 , 35 ]. These findings suggest minimum pack size policies may accomplish the intended effects of reducing access to low-cost products.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite a limited evidence base for cigars, policies mandating minimum pack sizes for cigars have been enacted in over 200 municipalities, primarily in Massachusetts, Minnesota, California, and New York [ 30 , 31 , 32 , 33 ]. Preliminary analyses of the effects of the policies enacted in Boston and Minnesota indicate the policies reduced single cigar availability, increased cigar sale price, and reduced disparities in access across neighborhoods [ 32 , 33 , 34 , 35 ]. These findings suggest minimum pack size policies may accomplish the intended effects of reducing access to low-cost products.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of communities in Massachusetts and Minnesota found that both single cigar availability decreased and cigar sale price increased after policy adoption. ( Brock et al, 2016 , Sbarra et al, 2016 , Li et al, 2017 , Kephart et al, 2019 ) However, those analyses examined the impact of minimum pack sizes of 2; it is unclear how larger pack sizes and price restrictions will shift market availability and price.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have examined marketplace changes following cigar pack policy adoption. Three studies examined the impact of policies adopted in Massachusetts ( Sbarra et al, 2016 , Li et al, 2017 , Kephart et al, 2019 ) while one examined the impact of policies adopted in Minnesota. ( Brock et al, 2016 ) In each of these studies, the parameters for minimum pack size and/or minimum price varied, but the findings consistently indicate the policies reduced the availability of single cigars in the policy communities.…”
Section: Introductionmentioning
confidence: 99%
“…Research gaps notwithstanding, more than 200 US local and state governments have imposed policies to curb small-quantity cigar packs, including cigarillos 28–30. Evidence suggests such local and state policies reduce cigar availability, increase price and can reduce cigar smoking disparities among youth and low socioeconomic status and high racial/ethnic minority communities where the prevalence of cigar use is higher 29–32. Nationally, the US Food and Drug Administration (FDA) has regulatory authority to address cigar pack quantity through the premarket review processes or by issuing pack quantity product standards 33.…”
Section: Introductionmentioning
confidence: 99%